Sex Trafficking in Cambodia - Schwartz, Abigail (Columbia Journal of Asian Law, 2004)
In 1999, a Dan Sandler, an American living in Cambodia, added a live bondage sex show to his pornographic web site. The site, named “Rape Camp,” featured “Asian sex slaves” who were used for “bondage, discipline and humiliation.” The Cambodian women on the site were blindfolded, bound, gagged, and some had clothespins attached to their nipples. The site also advertised Cambodia’s flourishing sex trade, for those who are “sick of demanding American bitches who don’t know their place.” It volunteered to help tourists find cheap flights, hotels, and brothels. It also offered advice for naYve first timers. “Don’t pay in advance,” it counseled, “and don’t be bashful about sending her back if she doesn’t do as advertised or if there is some major attitude shift.” When the site came to the attention of Mu Soucha, the Cambodian Minister of Women’s Affairs, she demanded Sandler’s arrest and prosecution under Cambodia’s new anti-trafficking laws. Facing a five-year sentence, Sandler appealed to the United States government, which eventually intervened, arranging for him to be deported rather than prosecuted under Cambodian law. Sandler’s case is emblematic of Cambodia’s pandemic sex trafficking problem. It illustrates the ubiquity of cheap sex sold throughout the country and the often violent and abusive atmosphere in which women are forced to work. For altogether too many women and girls, Cambodia has become a virtual “rape camp.” The country has one of the fastest-growing sex industries in the world. It portrays the government’s ambivalence and often conflicting attitude towards its burgeoning sex trade. The state tolerates the country’s numerous commercial sex outlets, which are mostly based on coerced labor. Yet, in the hopes of improving its human rights reputation in the international community, it cracks down on high profile cases with a strong hand. Sandler’s exoneration demonstrates the ultimate impotence of Cambodia’s anti-trafficking legislation and the general immunity of traffickers from legal consequences.